2017
DOI: 10.1007/s11427-017-9075-3
|View full text |Cite
|
Sign up to set email alerts
|

VdPKS1 is required for melanin formation and virulence in a cotton wilt pathogen Verticillium dahliae

Abstract: Verticillium dahliae is a soil-borne phytopathogenic fungus that causes vascular wilt disease in a broad range of hosts. This pathogen survives for many years in soil in the form of melanized microsclerotia. To investigate the melanin synthesis in V. dahliae, we identified a polyketide synthase gene in V. dahliae, namely VdPKS1. PKS1 is known to involve in the dihydroxynaphthalene melanin synthesis pathway in many fungi. We found that VdPKS1 was required for melanin formation but not for microsclerotial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…dahliae in hosts such as tobacco, tomato and lettuce (Wang et al ., ; Sarmiento‐Villamil et al ., ; Sarmiento‐Villamil et al ., ), but another study demonstrated that deletion of V . dahliae VdPKS1, a key factor for melanin production, resulted in reduced virulence on cotton (Zhang et al ., ). Undoubtedly, gene deletion studies of various MAPK cascade components suggest a strong correlation between melanin biosynthesis and virulence in V .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…dahliae in hosts such as tobacco, tomato and lettuce (Wang et al ., ; Sarmiento‐Villamil et al ., ; Sarmiento‐Villamil et al ., ), but another study demonstrated that deletion of V . dahliae VdPKS1, a key factor for melanin production, resulted in reduced virulence on cotton (Zhang et al ., ). Undoubtedly, gene deletion studies of various MAPK cascade components suggest a strong correlation between melanin biosynthesis and virulence in V .…”
Section: Discussionmentioning
confidence: 97%
“…The Vd8 strain cultured on MM was set as a control. Transcriptome profile analysis was done as described previously (Zhang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, albino mutants have been shown to have less fitness in the field, presumably due to the loss of melanin (23). In addition to protecting fungi from UV radiation, fungal melanins are potent virulence factors in both human-pathogenic (e.g., Cryptococcus neoformans [24], Fonsecaea pedrosoi [25], and A. fumigatus [26]) and plant-pathogenic (e.g., Venturia inaequalis [27] and Verticillium dahliae [28]) fungi.…”
mentioning
confidence: 99%